Case Report: The application of associating liver partition and portal vein ligation for staged hepatectomy in patients with hepatitis b virus-related hepatocellular carcinoma after undergoing treatment with an immune checkpoint inhibitor: a report of two cases - Ning, Cong; Liu, Guanmo; Zhang, Junwei; Yang, Xiaobo; Xu, Yiyao; Zhao, Haitao (Frontiers in Immunology, 2023)
Hepatocellular carcinoma (HCC) is often diagnosed at an unresectable stage without opportunities for curative therapy. Future liver remnant (FLR) insufficiency limits the range of patients who can undergo radical resection. Associating liver partition and portal vein ligation for staged hepatectomy (ALPPS) can ultimately achieve short-term hypertrophy of the FLR in patients with viral hepatitis-related fibrosis/cirrhosis and R0 resection. However, the influence of immune checkpoint inhibitors (ICIs) on liver regeneration remains unknown. We report two patients diagnosed with Barcelona Clinic Liver Cancer (BCLC)-B stage hepatitis B virus (HBV)-related HCC who underwent pioneering ALPPS after immunotherapy without posthepatectomy liver failure (PHLF). ALPPS has been shown to be safe and feasible in patients with HCC who underwent immunotherapy previously for the first time and might provide an alternative salvage option for future conversion therapy of HCC.